2011
DOI: 10.1093/hmg/ddr262
|View full text |Cite
|
Sign up to set email alerts
|

A new deletion refines the boundaries of the murine Prader-Willi syndrome imprinting center

Abstract: The human chromosomal 15q11-15q13 region is subject to both maternal and paternal genomic imprinting. Absence of paternal gene expression from this region results in Prader-Willi syndrome (PWS), while absence of maternal gene expression leads to Angelman syndrome. Transcription of paternally expressed genes in the region depends upon an imprinting center termed the PWS-IC. Imprinting defects in PWS can be caused by microdeletions and the smallest commonly deleted region indicates that the PWS-IC lies within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…The Cmv-cre transgene expresses Cre ubiquitously before implantation (12). Similar to paternal inheritance of a PWS-IC deletion (4,5), PWS-IC +/flox6kb Tg Cmv-cre pups were visibly smaller and had significantly lower birth weights than littermates ( Fig. 1 A and B).…”
Section: Deletion Of Pws-ic Before Implantation Results In Reduced Birthmentioning
confidence: 87%
See 2 more Smart Citations
“…The Cmv-cre transgene expresses Cre ubiquitously before implantation (12). Similar to paternal inheritance of a PWS-IC deletion (4,5), PWS-IC +/flox6kb Tg Cmv-cre pups were visibly smaller and had significantly lower birth weights than littermates ( Fig. 1 A and B).…”
Section: Deletion Of Pws-ic Before Implantation Results In Reduced Birthmentioning
confidence: 87%
“…Using a targeted deletion of a 35-kb region spanning Snrpn exons 1 to 6, we previously reported that the location and function of the PWS-IC is conserved in mice (4). More recently, we found that a 6-kb deletion surrounding Snrpn exon 1 yields an identical phenotype to the 35-kb deletion, demonstrating that all the functional elements of the PWS-IC are within this 6-kb region (5).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Deletions in the paternally inherited chromosome 15q11.2-13 region account for 70-75% of cases; 25-30% from maternal uniparental disomy (mUPD) and the remaining from mutations or defects of the IC (Cassidy and Driscoll, 2009;Butler, 2011;DuBose et al, 2011;McAllister et al, 2011; McCandless and The Committee on Genetics, 2011).…”
Section: Cause Of Pwsmentioning
confidence: 99%
“…Deletion or loss of function of PWS-IC on the paternal allele leads to abnormal methylation of the entire 2-Mb domain and inactivation of all PEGs, causing PWS (6). Deletion of a 6.0-kb sequence spanning SNRPN exon 1 in the mouse was recently shown to exhibit a complete PWS-IC deletion phenotype, as well (10). Deletion or inactivation of AS-IC on the maternal allele leads to an abnormal methylation pattern of PWS-IC, leading to activation of the paternally repressed genes, including the UBE3A antisense gene, thus inactivation of UBE3A and causing AS (4).…”
mentioning
confidence: 99%